Contractual issues of intellectual property rights (IPR) in construction projects implementing Building Information Modelling (BIM) Level 2 - Baharom, Mohammad Haniff; Abdullah Habib, Siti Nora Haryati; Ismail, Syuhaida (2020)
Building Information Modelling (BIM) is an emerging technology that provides a platform for a comprehensive digital representation of a facility to be created by integrating data from design conception until demolition. In seeking the optimum use of BIM, large degree of cooperation and collaboration among multi-disciplinary contributors are required for the digital data exchange and sharing process to be deployed. This situation, however, throws up new issues in delineating liabilities and limitations of contributors as the demarcation line of each contributor becomes unclear. In Malaysia, there is no known BIM-enabled standard form of contract that clearly preserves the intellectual property rights (IPR) of the BIM projects contributors. Therefore, the present study attempts to investigate the issues related to IPR in the context of BIM application in construction project. Qualitative methodology involving literature review, analysis of existing IPR provisions and semi-structured interviews with the experts were conducted. The research identified two major issues related to IPR in BIM projects: copyright ownership of the BIM model and data infringement. This paper is substantial to deliver knowledge to the construction industry practitioners regarding the legal and contractual considerations in the adoption of BIM.